السياق في التراث البلاغي العربي - عامر, سمية (universty of eloued جامعة الوادي, 2022)
الملخص: الحمد لله والصلاة والسلام على من لا نبي بعده، وبعد: فهذه الرسالة عنوانها "السياق في التراث البلاغي العربي دراسة في ضوء نظرية فيرث السياقية -مقاربة تداولية-، وتحتوي على أربعة فصول تسبقها مقدمة ، وتقفوها خاتمة: تناول الفصل التمهيدي مفاهيم عامة حول السياق والبلاغة والتداولية، وفي الفصل الأول: تناول السياق اللغوي في التراث البلاغي العربي، واشتمل على ثلاثة عناصر: أولهما السياق الصوتي، وثانيهما: السياق النحوي، وثالثهما: السياق الدلالي، وفي الفصل الثاني: تناول السياق غير اللغوي في التراث البلاغي العربي، واشتمل على عنصرين أولهما: السياق غير اللغوي في الدراسات الحديثة، وثانيهما: السياق غير اللغوي في التراث البلاغي العربي، حيث تناولنا في هذين العنصرين عناصر السياق غير اللغوي في النظرية، والتراث مع إبراز لأهمية النصوص التراثية التي أشارت إلى عناصر محددة للموقف كما في النظرية الغربية، كما تناولنا بالتحليل أهم العناصر التي تشتمل عليها المواقف كالمتكلم والمخاطب والزمان والمكان، ومعضدات الكلام وقيمتها في بناء النص وفهمه، وفي الفصل الثالث: تناول السياق بين التراث البلاغي العربي ونظرية فيرث ، واشتمل على أربعة عناصر أساسية، أولهما: المكون الاجتماعي "المقام"، وثانيهما: العلاقات الموقفية والبلاغة العربية، وثالثهما: العلاقة الداخلية، و"القواعد النظامية ونظرية النظم"، وربعهما الجملة الحالية، و"معاني النحو والصيغة النحوية"، وذيل البحث بخاتمة رصدت أهم النتائج، وقائمة المصادر والمراجع، ثم فهرس تفصيلي لما اشتملت عليه الرسالة. Abstract : Praise be to God, and prayers and peace be upon the one after whom there is no prophet, and after: This thesis is entitled "The Reality in the Arab Rhetorical Heritage on Firth's Contextual Theory - A Pragmatic Approach" The introductory dealt with general concepts about title, rhetoric and circulation, and in the first chapter: dealing with falsehood in the Arab rhetoric heritage, and it included three sections, the first usually in modern and heritage studies, the second: the grammatical context in modern and historical studies, and the third: semantics in modern studies, and the third: Perfumes and heritage, and in the second chapter: I dealt with justice in the Arab rhetorical heritage, and it included: The first of them: the non-linguistic in modern studies, and the second: the emergence of the non-linguistic in the Arab rhetorical heritage, where I dealt in counters: the non-linguistic elements in theory, and heritage With reference to the heritage origins contained in the instructions contained in the specific elements in Western theory, I dealt with the analysis of the most important elements in situations, situations such as the speaker, the addressee, time and place, biting speech and their value in building and understanding the text, and in the third chapter: a pragmatic approach between rhetorical heritage and Firth contextual theory And it included three basic topics, the first: the social component “Al Maqam”, the second: Situational Relationships and Arabic Rhetoric, and the third of them: the internal relationship, and “grammar”. Systematicism and Ecosystem Theory”, the current sentence, “the meanings of syntax and grammatical form”, the research appendix with a conclusion that notes the most important results, a list of sources and references, a list of foreign terms in the research, then an index of instructions for what the thesis contains.
دراسة في ضوء نظرية فيرث السياقية–مقاربة تداولية-
أطروحة دكتوراه في الاداب و اللغات تخصص لسانيات عامة
Keywords: السياق؛ السياق اللغوي؛ السياق غير لغوي؛ المقام: Context; linguistic context; non-linguistic context; current context